Weak Non-associative Structures of Groups with Applications - Shah Nawaz; Muhammad Gulistan; Naveed Yaqoob; Seifedine Kadry (International Journal of Analysis and Applications, 2019)
Inspiring by the weak symmetry occurring in the Hv-left invertive structures, in this article we have introduce a new class of Hv-LA-groups which is a generalization of LA-hypergroups. We have investigated different types of homomorphisms of Hv-LA-groups. Moreover, we have constructed the HvLA-groups. At the end a useful application of weak symmetry related with Hv-left invertive structure has been presented using the chemical redox reaction.